Meningkatkan Indeks Penjualan Thriftting Sepatu di Pasar Gelugur Rantau Prapat dengan Strategi Penerapan PrestaShop - Nasution, Fahri Emil Afandi; Harahap, Syaiful Zuhri; Nasution, Marnis (Journal of Computer Science and Information System(JCoInS), 2024)
To increase the sales index of Budi Shoes Thrift in the Glugur Rantauprapat market, this research will start developing e-commerce using CMS Prestashop. Data will be collected through observation and interviews with the owner of Budi Shoes Thrift.to understand customer preferences and buying and selling activities. Even though Prestashop allows easy online transactions, most users prefer to buy directly in store or use dropship services. The level of consumer trust in well-known local brand goods is the main component that influences this. Although Prestashop has tremendous potential to increase market and operational efficiency, effective promotion and outreach strategies are required to achieve success. The right strategy, which combines technology and increases customer trust, can drive Prestashop implementation, increase sales and strengthen market share.